Ethnobotanical analysis of medicinal and cosmetic plants using use value and informant consensus factor in Blitar - Sofiyana, Marinda Sari; Amarlita, Dhamas Mega; Ningrum , Pipit Mustika (Edubiotik : Jurnal Pendidikan, Biologi dan Terapan, 2025)
Traditional medicinal and personal care plant use remains an important component of community health practices in rural Indonesia, yet integrated quantitative ethnobotanical documentation is still limited. This study aimed to identify plant species used for medicinal and cosmetic purposes, document their parts and preparation methods, and analyze their cultural importance using quantitative ethnobotanical indices. A qualitative descriptive ethnobotanical design was applied through semi-structured interviews and participatory field observations involving 30 informants across 20 sites in Talun and Doko, Blitar. Data were analyzed using Use Value (UV) and Informant Consensus Factor (ICF) to evaluate species importance and agreement levels among informants. A total of 25 plant species from 19 families were recorded, with leaves as the most frequently utilized plant part and internal medicine as the dominant use category. The highest UV values were found in Peperomia pellucida (0.87) and Physalis angulata (0.80). The highest consensus occurred in eye care (ICF = 1.00), followed by internal medicine and skin treatment (ICF = 0.83). These results indicate strong cultural reliance and shared knowledge patterns in local plant use. The findings provide quantitative support for prioritizing culturally important species and offer applied potential for biodiversity conservation and contextual biology education.